Lipid Mediators Are Critical in Resolving Inflammation: A Review of the Emerging Roles of Eicosanoids in Diabetes Mellitus - Tessaro, Fernando H. G. (Biomed Res Int, 2015)
The biosynthesis pathway of eicosanoids derived from arachidonic acid, such as prostaglandins and leukotrienes, relates to the pathophysiology of diabetes mellitus (DM). A better understanding of how lipid mediators modulate the inflammatory process may help recognize key factors underlying the progression of diabetes complications. Our review presents recent knowledge about eicosanoid synthesis and signaling in DM-related complications, and discusses eicosanoid-related target therapeutics.